EFFECT OF COATING TABLE EGGS WITH NATURAL OILS AND STORAGE CONDITIONS ON ITS SHELF LIFE - Al-Shadeedi, Shahrazad M. J. (The Iraqi Journal of Veterinary Medicine, 2010)
The object of this study was to evaluate coating table eggs with different medicinal oils and their effects on shelf life properties of fresh eggs. After storage for 1, 2, 4 and 8 weeks at room temperature (experiment 1) and refrigerator temperature (experiment 2) . Fresh table eggs were collected from a flock of Isa brown laying hens, the eggs were distributed into four groups as follow :-1-Control group 2-Corn oil group 3-Dill oil group 4-Black seed oil group, the eggs were coated by immersioned in oil at 56.7 C for16 min (Oil thermostabilization) . The results revealed that coating table eggs with oils in general and specially medicinal oils reduced the mean decrease in egg weight , egg weight loss , PH , free fatty acids , total bacterial count and fungi count after storage for 1, 2, 4 and 8 weeks compared with the control . Control group eggs expired after 8 weeks of storage at room conditions according to Iraq standard specification for eggs.The significant reduction in shelf life properties of the eggs treated with natural oils started at the second week under room temperature storage, and fourth week under refrigerator temperature. Dill oil or black seed oil thermo stabilization for table eggs were better than corn oil in reduced the reduction of shelf life after storage at room or refrigerator temperatures. Conclusion, coating locally produced or imported table eggs with medicinal oils to prevention the eggs from deterioration and spoilage during storage.